Sociedade da notificação: a dignidade humana no meio ambiente digital - Silva, Elaine Rodrigues Jerônimo (2022)
This dissertation aims to seek, in the principles of human dignity and intergenerational solidarity, a way out for an improved digital world. In this world, reality is liquid; highly technological and fragmented. There is an urgent need for a digital (omni)presence, the consumption of online information, concern for likes and notifications, purchases influenced by sponsored links, the instantaneous sharing of information (and misinformation) through messaging applications, or repetitive and standardized dances on social networks. Thus, the question arises: given the lack of regulatory intervention on digital platforms, is there a way to enhance a healthy environment and the principle of human dignity on the Internet? Indeed, the study is justified by the relevance of reflection on the healthiness of the digital environmental space and the interdisciplinarity of the theme, being connected to the human, technological and economic sciences. The adopted methodology is based on the mixed methods of Creswell and Clark Plan. The main objective of the study is to identify a possible legal-administrative solution to the issue of degradation in the digital environment, considering the lack of normative instruments in the scenario of regulation of technology industry products. Specifically, the study aims to verify updates in the notion of human dignity in the information society, establish a dialogue between the use of artificial intelligence and the serial standardization of the cultural behavior of individuals; and finally, to evaluate the feasibility of fundamental rights and the principles of Environmental Law as regulatory benchmarks for digital platforms, considering, among others, the teaching of Paulo Affonso Leme Machado, Wolfgang Hoffmann-Riem, Ingo Sarlet, Manuel Castells, Milton Santos and Hans Jonah. The hypothesis defended in this study seeks to recognize quality internet access as a fundamental right and the regulation of digital platforms as an essential action.